Penyuluhan dan Praktek Perilaku Hidup Bersih dan Sehat di SD Islam Cokroaminoto 1 - Santi Santi; Herawati Ramli; La Ode Swardin (ADMA : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2022)
Clean and healthy living behavior in the school environment is a set of behaviors practiced by students, teachers, and the school community as a result of learning. Problems that arise in elementary schools show that students do not practice PHBS such as rarely washing their hands with running water and soap, Disposing of garbage in its place, Doing physical activity every day so that there are several cases of diseases such as diarrhea, intestinal worms, typhoid, and ulcers. . The method used in this community service is community development, the results of the PKM Activities with Clean and Healthy Living Behavior (PHBS) for school children carried out at SD Islam Cokroaminoto 1 run smoothly. All students enthusiastically participated in this activity so that this PKM activity has been able to increase students' awareness and knowledge so that they can practice Clean and Healthy Living behavior in their daily lives, and it is hoped that in the future the knowledge they have gained can be applied continuously in their family life so that all can be healthy and create optimal health degrees.